Acute changes in acceleration phase sprint biomechanics with lower body wearable resistance. Issue 10 (26th November 2022) - Simperingham, Kim David; Cronin, John B; Ross, Angus; Brown, Scott R.; Macadam, Paul; Pearson, Simon
ABSTRACT: The aim of this acute cross-sectional study was to quantify the kinematic and kinetic changes that occur during sprint acceleration when lower body WR is worn. Fifteen male rugby athletes (19 years; 181 cm; 91 kg) were assessed during maximal effort over−ground and treadmill sprinting over 20 m under three different loading conditions: 0%, 3% and 5% body mass (BM) added weight attached to the lower body. Treadmill data provided a convenient estimate of kinetic changes in the absence of in-ground force plates. The loaded conditions resulted in significantly increased ground contact time (5 to 6%) and decreased step frequency (−2 to −3%) during sprint accelerations (effect size = 0.32–0.72). Moderate WR loading (3% BM) resulted in increased (9%; effect size = 0.66) theoretical maximum horizontal force (relative to BM) and unchanged 20 m sprint times (p > 0.05). Heavier WR loading (5% BM) resulted in a significant decrease (−4%) in vertical ground reaction forces (relative to total system mass) and slower (1 to 2%) 20 m sprint times (effect size = 0.38–0.70). Lower body WR loading up to 5% BM can provide specific sprint training overload, while affecting sprint acceleration biomechanics by ≤ 6%.